Using combinatorial maps for algorithms on graphs - Cori, Robert (Journal of Computer Science and Cybernetics, 2021)
The aim of this paper is to come back to a data structure representation of graph by permutations. This originated in the years 1960-1970 by contributions due to J. Edmonds [7], A. Jacques [11], W. Tutte [22] in order to consider the embedding of a graph in a surface as a combinatorial object. Some algebraic developments where suggested in [4] and [12]. It was also used for implementation in different situation, like planarity testing by H. de Fraysseix and P. Rosenstiehl [6], computer vision by G. Damiand  and A. Dupas [5] or formal proofs by G. Gonthier [9].